Rapid Onsite Visual Detection of Orf Virus Using a Recombinase-Aided Amplification Assay - Huan Cui; Jiyu Guan; Huijun Lu; Jun Liu; Fei Tu; Cheng Zhang; Kai Su; Zhendong Guo; Kui Zhao (Life, 2023)
Orf is an important zoonotic disease caused by the Orf virus (ORFV) which can cause contagious pustular dermatitis in goats and sheep. Orf is widespread in most sheep-raising countries in the world, causing huge economic losses. Although diagnostic methods for ORFV infection already exist, it is still necessary to develop a time-saving, labor-saving, specific, low-cost and visual diagnostic method for rapid detection of ORFV in the field and application in grassroots laboratories. This study establishes a DNA extraction–free, real-time, visual recombinase–aided amplification (RAA) method for the rapid detection of ORFV. This method is specific to ORFV and does not cross-react with other common DNA viruses. The detection limits of the real-time RAA and visual judgment of the RAA assay at 95% probability were 13 and 21 copies per reaction for ORFV, respectively. Compared with qPCR, the sensitivity and specificity of the real-time RAA assay were 100%, and those of the visual RAA assay were 92.31% and 100.0%, respectively. The DNA extraction–free visual detection method of RAA established in this study can meet the needs of rapid onsite detection and grassroots laboratories and has important reference value and significance for the early diagnosis of diseased animals.